Selected heavy metal concentrations in Lates calcarifer and water in aquaculture farm from Tuaran, Sabah - Hee, Shiau Fei (2015)
This research was performed to determine the concentration of heavy metals (Cu, Zn, Cd, Fe and Pb) in water and Lates calcarifer (gills and muscle) in the aquaculture farm and to investigate the relationship between heavy metals in water and Lates calcar/fer. The results obtained were compared with the standard permissible values in Food Act 1983. The heavy metal concentration were analysed by ICP-OES after the process of digestion. None of the metal concentration obtained exceeds the standard values in Food Act 1983. Some of the metal concentrations were undetectable in water and gills samples; Cd, Cu and Pb in water and Cd in gills. The concentration for metal content detected in water sample was between 0.0068 mg/kg to 0.0097 mg/kg Pb while there was 0.0008 mg/kg to 0.0033 mg/kg Zn. For muscle sample, Cd range from 0.0800 mg/kg to 0.1150 mg/kg; Cu range from 0.6850 mg/kg to 0.9100 mg/kg; Fe range from 22.4400 mg/kg to 109.5450 mg/kg; Pb range from 0.3900 mg/kg to 0.8685 mgjkg and Zn range from 27.7100 mgjkg to 34.9850 mgjkg. For gills sample, Cu range from 0.0700 mg/kg to 0.9850 mg/kg; Fe range from 101.6100 mg/kg to 119.7550 mg/kg; Pb range from 0.5250 mgjkg to 0.9400 mg/kg and Zn range from 75.0450 mg/kg to 83.9000 mg/kg. Bioconcentration factor calculated indicates that Pb and Zn have accumulated in the gills and muscle of the species selected while the correlation analysis also shown that the heavy metals analyzed in this study has significant effect to the water as well as to the fish species.